Ecological Civilization Education: an Indispensable Part of China’s Ecological Civilization Construction Road - Boliang ZHANG; Yusen DONG; Dongliang LI (PT Keberlanjutan Strategis Indonesia, 2024)
In the context of global sustainable development (SD) and China's ecological civilization construction (ECC), China has entered a new era of change, and its social, economic and environmental development is moving toward SD. However, due to inadequate understanding of the root causes of environmental problems, in the process of promoting the ECC, the key role of education in this process is ignored. At the same time, the United Nations (UN) clearly pointed out that education is extremely important in promoting SD and increasing the capacity of people to solve the environment and development issues in the agenda in 21st century. Integrating the concept of ecological civilization into education plays a crucial role in solving environmental problems. However, with the popularization of ecological civilization education (ECE) and the deepening of research, its existing problems are becoming more and more obvious, so it is necessary to make a systematic plan for the development of ECE. By reviewing the historical process of ECD development, this paper aims to discover the important role of ECD in China's ECC process and the realization of SD, discusses the relevant prospects and challenges of ECE, and summarizes and puts forward the policy and enlightenment for the future development of ECE in China. This paper contributes to the ongoing discussion on education to address environmental or development issues, enabling relevant policy makers and stakeholders to see the present or future opportunities and complexities of ECD and make the right choices.